(untitled) (Global Journal of Human-Social Science, 2020)
This study explains how Bangladeshi media responded during the coronavirus crisis focusing on the issues of news related to COVID-19. The study analyzes the content of a total of 744 articles in the ProthomAlo & The Daily Star, the country’s most-read newspapers in-between the timeline from 8th March 2020 to 4th April 2020. It investigates how the COVID-19 presented as `furious’ and `deadly’ virus among the readers. In particular, this study explores the representation pattern of the phenomena of ’emerging deadly infectious diseases’ in the newspapers. Using Social Representation Theory (SRT), the study investigates the collective meaning sharing focus on the news coverage during the early stage of the COVID-19 outbreak in Bangladesh. The study also finds out how the newspapers sideline the representation of this pandemic as a `health crisis’ to ` national economic crisis.’ Thus the representation covers up the government irresponsibility by focusing more on `unconscious mass’ and `limitations’ of a developing country. Therefore, the `panic’ increases and the solution of this pandemic muffled under it. Also, this study provides some tentative explanations for this linguistic representation by editorial sections of these newspapers.